2014
DOI: 10.1128/aem.02920-13
|View full text |Cite
|
Sign up to set email alerts
|

Intersubspecific Recombination in Xylella fastidiosa Strains Native to the United States: Infection of Novel Hosts Associated with an Unsuccessful Invasion

Abstract: The bacterial pathogen Xylella fastidiosa infects xylem and causes disease in many plant species in the Americas. Different subspecies of this bacterium and different genotypes within subspecies infect different plant hosts, but the genetics of host adaptation are unknown. Here we examined the hypothesis that the introduction of novel genetic variation via intersubspecific homologous recombination (IHR) facilitates host shifts. We investigated IHR in 33 X. fastidiosa subsp. multiplex isolates previously identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 53 publications
(123 reference statements)
4
71
0
Order By: Relevance
“…In this specific case, however, the use of the strain of subspecies fastidiosa being tested in the USA in the EU would represent the introduction of novel X. fastidiosa genetic diversity into the risk assessment area. This could be an important problem because of the very high rates of X. fastidiosa recombination rates in the field (Nunney et al, , 2014 and laboratory (Kung andAlmeida 2011, 2014); in other words, recombination between the genotype present in Apulia, Italy, and any novel genotype could lead to recombination and eventually the emergence of new diseases. Furthermore, the strategy of using avirulent strains to fight X. fastidiosa infections may be counterproductive, as changes in virulence or reversions of avirulent strains may occur through lateral gene transfer, a phenomenon well known to occur in X. fastidiosa (e.g.…”
Section: Control Of the Disease In Plantamentioning
confidence: 99%
See 4 more Smart Citations
“…In this specific case, however, the use of the strain of subspecies fastidiosa being tested in the USA in the EU would represent the introduction of novel X. fastidiosa genetic diversity into the risk assessment area. This could be an important problem because of the very high rates of X. fastidiosa recombination rates in the field (Nunney et al, , 2014 and laboratory (Kung andAlmeida 2011, 2014); in other words, recombination between the genotype present in Apulia, Italy, and any novel genotype could lead to recombination and eventually the emergence of new diseases. Furthermore, the strategy of using avirulent strains to fight X. fastidiosa infections may be counterproductive, as changes in virulence or reversions of avirulent strains may occur through lateral gene transfer, a phenomenon well known to occur in X. fastidiosa (e.g.…”
Section: Control Of the Disease In Plantamentioning
confidence: 99%
“…It has been shown that the strain present in Italy is very homogeneous, and identical to a variant infecting oleander in Costa Rica. This also represents the first report of subspecies pauca in Costa Rica (Nunney et al, 2014). It was assigned a new sequence type (ST) profile, ST 53, and named CoDiRO for "Complesso del Disseccamento Rapido dell' Olivo".…”
Section: Current Situation In Italy (Apulian Situation)mentioning
confidence: 99%
See 3 more Smart Citations